The Effect of Flow Velocity on Corrosion and Corrosion Mitigation of Carbon Steel in Wide Range of Sulfuric Acid Concentration - Alzuraiji, Saher; Kazem, Maha H.; Hasan, Basim O.; Znad, Hussein T. (Al-Nahrain Journal for Engineering Sciences, 2024)
The impact of flow velocity (0-900 rpm) on the corrosion rate of carbon steel in a wide range of sulfuric acid concentrations (0-90% in H2O) at 30 °C and 1 h was studied and discussed. In addition, the efficiency of corrosion inhibitor (dimethyl disulfide, DMD) was evaluated in hardest corrosion conditions for the range of velocity investigated. The results revealed that increasing the flow velocity of H2SO4 solution, increases the corrosion rate depending on the acid concentration. When the flow velocity is increased of H2SO4 solution, the corrosion potential was shifted to more negative. The DMD inhibitors showed significant inhibition efficiency at high velocities, where the highest percentage of inhibitor efficiency reached 98% at 900 rpm.